2009
DOI: 10.1051/0004-6361/200912551
|View full text |Cite
|
Sign up to set email alerts
|

HD 172189: another step in furnishing one of the best laboratories known for asteroseismic studies

Abstract: HD 172189 is a spectroscopic eclipsing binary system with a rapidly-rotating pulsating δ Scuti component. It is also a member of the open cluster IC 4756. These combined characteristics make it an excellent laboratory for asteroseismic studies. To date, HD 172189 has been analysed in detail photometrically but not spectroscopically. For this reason we have compiled a set of spectroscopic data to determine the absolute and atmospheric parameters of the components. We determined the radial velocities (RV) of bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…14and the values of mass, radius, rotation, inclination, and/or projected velocity (v sin i) provided by the different authors (see Table 2). Two of these δ Scuti stars, CID 1043 (star 1) and CID 8170 (star 6), are well-known spectroscopic binaries whose structural and orbital parameters were studied by Hareter et al (2014) and Creevey et al (2009), respectively. The δ Scuti star with chemical peculiarities studied by Escorza et al (2016), CID 5685 (star 4), is a good example of the observed difference in temperature when two different methods are used.…”
Section: The Case Of the Well-known δ Scuti Starsmentioning
confidence: 99%
“…14and the values of mass, radius, rotation, inclination, and/or projected velocity (v sin i) provided by the different authors (see Table 2). Two of these δ Scuti stars, CID 1043 (star 1) and CID 8170 (star 6), are well-known spectroscopic binaries whose structural and orbital parameters were studied by Hareter et al (2014) and Creevey et al (2009), respectively. The δ Scuti star with chemical peculiarities studied by Escorza et al (2016), CID 5685 (star 4), is a good example of the observed difference in temperature when two different methods are used.…”
Section: The Case Of the Well-known δ Scuti Starsmentioning
confidence: 99%
“…In the case of the eclipsing binary HD 172189, the spectra were very useful for identifying the δ Scuti component (see Fig. 4) and disentangling the stars (Creevey et al 2009).…”
Section: Binary Systemsmentioning
confidence: 99%
“…First, through the spectra it is possible to derive constraints on the component masses (e.g. Tango et al 2006;Vučkovic et al 2007;Creevey et al 2009;Desmet et al 2010), which is valuable information for seismic models and models on stellar structure and (binary) evolution. Second, in the case of doublelined spectroscopic binaries it is possible to disentangle the component spectra (Harmanec et al 2004) and to study the line-profile variability of the disentangled components in full detail .…”
Section: Ground-based Time-seriesmentioning
confidence: 99%